2012
DOI: 10.12693/aphyspola.122.174
|View full text |Cite
|
Sign up to set email alerts
|

AC Electrical Conductivity and Dielectric Properties of Perovskite (Pb,Ca)TiO3Ceramic

Abstract: Pb1−xCaxTiO3 perovskite crystalline structure with x = 0, 0.2, 0.6, 0.7, and 0.8 were prepared by mixture method. The ac conductivity and dielectric properties of the studied bulk compositions have been investigated in the frequency range 1 × 10 3 5 × 10 6 Hz and temperature range 303473 K. The experimental results indicate that the ac conductivity σac(ω), dielectric constant ε ′ and dielectric loss ε ′′ depend on the temperature and frequency. The ac conductivity was found to obey the power law ω S with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 30 publications
(27 reference statements)
4
35
0
Order By: Relevance
“…Such field will cause some ordering or orientation in samples, the molecular dipoles cannot orient themselves at low temperature, when the temperature is increased the dipole orientation is facilitated and dielectric constant increases. The strong frequency dispersion of permittivity is observed in the low frequency region followed by a nearly frequency independent behaviour above 10 KHz .The peak in the graph can be attributed to strong relaxation contribution leading to high dielectric constants and therefore electronic and ionic polarizablity [12].The negative dielectric constant observed at some frequencies for some wt.percentage is due DOI: 10.9790/4861-0805028390 www.iosrjournals.org 86 | Page to its reduced plasma frequency and an induction effect. The magnitude of the negative dielectric constant and the resonance frequency are tunable by dopant type and doping composition.…”
Section: Dielectric Constantmentioning
confidence: 91%
“…Such field will cause some ordering or orientation in samples, the molecular dipoles cannot orient themselves at low temperature, when the temperature is increased the dipole orientation is facilitated and dielectric constant increases. The strong frequency dispersion of permittivity is observed in the low frequency region followed by a nearly frequency independent behaviour above 10 KHz .The peak in the graph can be attributed to strong relaxation contribution leading to high dielectric constants and therefore electronic and ionic polarizablity [12].The negative dielectric constant observed at some frequencies for some wt.percentage is due DOI: 10.9790/4861-0805028390 www.iosrjournals.org 86 | Page to its reduced plasma frequency and an induction effect. The magnitude of the negative dielectric constant and the resonance frequency are tunable by dopant type and doping composition.…”
Section: Dielectric Constantmentioning
confidence: 91%
“…The variation of \n" with the temperature corresponds to a thermally activated process. 17 The conduction mechanism can be explained by the correlated barrier hopping (CBH) model till 400 C. At higher temperatures \n" has temperature-independent behavior which can be explained by the quantum tunneling model. Hence it can be concluded that similar charge barriers are responsible for both conduction and relaxation process in the sample Pb 2 Sr 2 CaCu 2 O 9 .…”
Section: Ac Conductivitymentioning
confidence: 99%
“…Electrical behaviors of complex ionically conducting materials plotted as a function of frequency and¯rst reported by Jonscher 15,16 are known as universal dielectric response (UDR). 17 The investigations performed into electrical properties of ceramic composites at alternating currents have con¯rmed that current conduction within a certain frequency range is realized by hopping exchange of electrons. [18][19][20] The objective of the present work is to study the dielectric and electrical impedance properties of the sample Pb 2 Sr 2 CaCu 2 O 9 in the range of frequencies (42 Hz-1 MHz) at di®erent temperatures with a view to understand the conductivity mechanisms involved in this new material.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperature, the dipoles cannot orient themselves. When the temperature is increased the orientation of the dipoles is facilitated and this increases the value of orientational polarization, which leads to an increase of ε 1 with temperature [25,26].…”
Section: Dielectric Properties and Ac Conductivitymentioning
confidence: 99%